1982
DOI: 10.1016/0143-1471(82)90143-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of a surplus production model to assess environmental impacts on exploited populations of Daphnia pulex in the laboratory

Abstract: The surplus production model is a simple and easily applied model for the assessment of environmental impacts on exploited fish populations. However, its application requires several assumptions about the relationships between the degree of impact and the population response that are dijficult to test using field data. To examine these assumptions, the model is applied to exploited laboratory populations of Daphnia pulex exposed to chronic radiation stress. The model describes the observed relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Some examples are oil pollution in the seas [19], degradation of forests [24,21], dumping of toxic waste in rivers and lakes [9,14] and the environmental fluctuation due to eutrophication in the Salton sea [3,7] causing pelican extinction.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are oil pollution in the seas [19], degradation of forests [24,21], dumping of toxic waste in rivers and lakes [9,14] and the environmental fluctuation due to eutrophication in the Salton sea [3,7] causing pelican extinction.…”
Section: Introductionmentioning
confidence: 99%
“…This logistic surplus production model was developed by Volterra (1928), Hjort and others (1933), Graham (1935), and Schaefer (1954). It has been widely applied for stock assessment (Ricker 1975, Gulland 1972and 1977, Jensen 1976and 1978, Abramson and Tomlinson 1972, and MacCall and others 1976, for environmental impact assessment (Jensen 1982, Jensen andothers 1982), and for assessment of the impact of toxicants on populations Marshall 1982 and1983).…”
Section: The Modelsmentioning
confidence: 99%
“…Most of the previous work assumed that input of toxicant was continuous. The toxicants, however, are often emitted to the environment with regular pulse [9]. A lot of data have indicated that the use of agriculture chemicals may cause potential harm to the health of both human beings and living beings.…”
Section: Introductionmentioning
confidence: 99%